Analisis Hukum Coulomb Dalam Dinamika Muatan Listrik - Clara Ester Nikmat Gulo; Nethania Nonifati Roselin Gea (CV. SINAR HOWUHOWU, 2024)
The background to this research focuses on Coulomb's law, which is a basic principle in physics that explains interactions between electric charges. This law is very important in understanding various electrical and magnetic phenomena that occur in nature. In the context of electric charge dynamics, a deep understanding of Coulomb's law can provide better insight into interactions between charges in various technological applications, such as in electronics and telecommunications.The aim of this research is to analyze existing literature on Coulomb's law and its application in electric charge dynamics. This research aims to identify various relevant aspects of Coulomb's law and how this principle is applied in real situations. The research method used is literature analysis, where the author collects and analyzes various academic sources, journal articles and books that discuss Coulomb's law and its applications. This process involves data collection, synthesis of information, and presentation of results in the form of a structured narrative.The research results show that Coulomb's law not only provides a theoretical basis for the interaction of electric charges, but also plays an important role in the development of modern technology. This research finds that a better understanding of Coulomb's law can improve efficiency in the design of electrical devices and communications systems.The conclusions of this research confirm the importance of Coulomb's law in the dynamics of electric charges and its application in various fields. It is hoped that the results of this literature analysis can become a reference for further research and technological development related to electric charges.